2012
DOI: 10.1002/rnj.00013
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Barriers and Disability

Abstract: There is evidence that early detection from breast cancer screening is an effective means to reduce overall mortality from breast cancer. Findings from multiple research studies suggest that women with chronic disabling conditions are less likely to participate in breast cancer screening due to the multiple barriers they face. Barriers include those related to finances, environment, physical limitations, health care providers’ attitudes and lack of knowledge, and psychosocial issues. The purpose of this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…This result is in line with previous findings 32,33 in which younger patients with BC and positive axillary lymph nodes presented an increased risk of death. 35 The present population-based study showed that BC survival tended to improve in Côte d'Or between 1998 and 2009. This result is in agreement with those reported in a recent study, in which comorbidities had a significant impact on survival after BC, with poorer survival among older patients with one or more comorbid conditions.…”
Section: Discussionmentioning
confidence: 55%
“…This result is in line with previous findings 32,33 in which younger patients with BC and positive axillary lymph nodes presented an increased risk of death. 35 The present population-based study showed that BC survival tended to improve in Côte d'Or between 1998 and 2009. This result is in agreement with those reported in a recent study, in which comorbidities had a significant impact on survival after BC, with poorer survival among older patients with one or more comorbid conditions.…”
Section: Discussionmentioning
confidence: 55%
“…Although the current study did not investigate the reasons for such disparities, previous studies have suggested several factors as barriers to breast cancer screening related to disability: 1) system factors (eg, inaccessible facilities or equipment, transportation problems, insurance coverage or economic issues); 2) provider factors (eg, poor knowledge of disability, negative stereotyping and social misconceptions, and failure to recommend preventive services); and 3) patient factors (eg, disability‐specific barriers [eg, communication], competing health issues, lack of awareness or knowledge, misperceptions regarding screening, and lack of a usual source of care).…”
Section: Discussionmentioning
confidence: 97%
“…21 Currently, the majority of national-level interventions to increase breast cancer screening rates do not address the needs of women with disabilities, and greater efforts are needed to develop policy actions specific to their needs. Such efforts include providing accessible information and education, 29 ensuring accessible screening equipment such as wheelchair-accessible mammography machines, 20,29,39 support for transportation, 29 additional examination time and technician support, and navigation by health care professionals such as rehabilitation nurses. 29 A usual source of care was reported to increase the use of clinical preventive services, including breast cancer screening, in women with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand women in remote areas have only limited access to alternatives and hence they just simply prefer dropping out the system which they feel as hostile rather than dealing with it. (Todd & Stuifbergen, 2012). Another reason for people for neglecting screening is related to the lack of physician recommendation (Othman et al, 2013).…”
Section: Breast Cancer Screeningmentioning
confidence: 99%